POLA PENGGUNAAN OBAT ANTI HIPERGLIKEMIK ORAL PADA PASIEN DIABETES MELITUS TIPE 2 RAWAT INAP DI RUMAH SAKIT X PEKANBARU TAHUN 2014 - Firni Dwi Sari; Inayah "; Muhammad Yulis Hamidy (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2016)
ABSTRACTOral anti-hyperglycemic drug is one of the pharmacological treatment of type 2diabetes melitus (DM).Oral anti-hyperglycemic is use when the patient fails to respondat least three months of carbohydrates low diet and energy with physical activity is recommended, after which efforts lifestyle changes, the blood glucose levels constant above 200 mg/dL and HbA1c above 6.5%. This study was purposed to determine the pattern of oral anti-hyperglycemic in hospitalized patients with Type 2 Diabetes Melitus at Ibnu Sina Islamic Hospital Pekanbaru at 2014. The type of research was descriptive. The samples are 65 people included all hospitalized patients with type 2 diabetes melitus according to inclusion and exclusion criteria. Data retrieved from the medical records of hospitalized patients with type 2 diabetes melitus in Ibnu Sina Islamic Hospital Pekanbaru period from January to December 2014. The most characteristics of subject was average of age 56.83 (± 10.84) years, the average of random blood glucose level 290.91 (± 124.5) mg/dL, female sex (55.4%), not working (39.6%), BPJS and personal finance (46.2%), and diagnosis of hospitalized patients type 2 diabetes melitus with other diseases (49,2%). The most oral anti-hyperglycemic drug used is inhibitor of gluconeogenesis (54.1%), the most daily doses of oral anti-hyperglikemic drug was metformin 1000 - 1500 mg/day (35,4%). The most administration of oral anti-hyperglikemic drug is oral single drug (60%).Keywords: pattern, oral anti-hyperglycemic drug, type 2 diabetes melitus